PERAN KEUNGGULAN KOMPETITIF DALAM PEMASARAN PRODUK DENGAN PENERAPAN MEDIA SOSIAL DI ERA GLOBAL PADA UKM SEPATU BUNUT DI KABUPATEN ASAHAN - Dina Audiva Adawiyah; Wahdatun Thoibah; Fitri Thoibah; Suhairi Suhairi (Universitas Labuhanbatu, 2022)
This study aims to determine the relationship of cooperation as a social network for the artisans of UMKM Shoes Bunut and the economic relationship of the community which is related to business continuity. This research was conducted through a quantitative approach. The location of this research is Asahan district because it has more number of UKM Shoes Bunut which has internationalized compared to other districts in the province. The subjects in this study were the owners or managers of the Shoes Bunut UKM in Asahan Regency. and the object of this research is internationalization which is influenced by the role of competitive advantage. The results in this study are Social Media used as a Marketing Tool Social media used by respondents to market products are Instagram (78%), Youtube (58%), Facebook (31%), Line (20%), WhatsApp (18% ), Path (7%), and Twitter (2%). it can be concluded if all hypotheses in this study are accepted and have a positive and significant effect.